Evolution and distribution of resistance genes and bacterial community in water and biofilm of a simulated fish-duck integrated pond with stress. (April 2020) - Zhou, Min; Xu, Yanbin; Ouyang, Pengqian; Ling, Jiayin; Cai, Qiujie; Huang, Lu; Zhou, Xiao; Zheng, Li
Abstract: Integrated fish-duck pond is a common circular farming model in South China, besides, it is also hot-spot for the co-selection of antibiotic resistance genes (ARGs). The aim of this study was to investigate the effects of duck manure, As and cefotaxime on the bacterial community, and the evolution and distribution of ARGs and metal(loid) resistance genes (MRGs) in water and biofilm. Five groups of fish tanks included a control and four test groups. The experimental period lasted for 100 days. Six ARGs ( CIT, DHA, EBC, FOX, MOX, TEM ), two MRGs ( ars B, ars C), and two integron genes ( intI 1, intI 2) were tracked and detected in water and biofilm. The results showed that duck manure brought ARGs and MRGs into fish tanks. Stress factors (cefotaxime, As) increased the relative abundance of resistance genes, and this was positively correlated with stress concentrations. The biofilm was visible significantly at the end of stage 3, and the total relative abundance of resistance genes in biofilm was higher than water from stage 5 onwards. Evolution of AmpC β-lactamase resistance genes was more obvious than MRGs, especially for MOX, which increased by 3 orders of magnitude. The abundance of Flavobacterium was higher in biofilm than in water. Moreover, correlation analysis showed that both ars B and MOX were significantly correlated with intI 1 (p < 0.05), which suggested a potentially dissemination risk of resistance genes. This study provides a reference for health risk assessment in integrated aquaculture environment contaminated with duck manure, antibiotics and metalloids. Graphical abstract: Image 1 Highlights: Duck manure brought antibiotic and As resistance genes (RGs) into fish ponds. Stress factors significantly increased relative abundance of RGs in tanks (p < 0.05). Most RGs in biofilm gradually increased and then were more abundant than in water. MOX should be noted for its most significant positive to all stress factors. No significant correlation was observed between cefotaxime and As RGs.